Transfer of Adoptive Immunity to Tuberculosis in Mice - Lefford, Maurice J. (1975)
A system is described for studying adoptive immunity to tuberculosis in syngeneic mice. Donor mice were immunized with 10(4) BCG intravenously, and lymphoid cells were harvested 28 days later. Adoptive immunity was measured in recipient mice in terms of the inhibition of growth of BCG in the liver and spleen following intravenous injection. Adoptive immunity was expressed optimally when recipients were sublethally irradiated (500 R), challenged with 10(4) to 10(5) viable organisms, and given sensitized lymphoid cells intravenously. Adoptive immunity was not manifest until 14 days after challenge and was effective against Mycobacterium tuberculosis H37Rv as well as BCG. Immunity could be conferred by spleen, lymph node, peritoneal exudate, and resident peritoneal (washout) cells. The lymphoid cells conferring immunity were shown to be thymus-dependent lymphocytes by virtue of their nonadherence to glass wool and sensitivity to anti-θ serum plus complement. The sensitized cells were relatively susceptible to both in vitro and in vivo X-irradiation.